FENOMENA BAHAYA INVESTASI ILEGAL PADA APLIKASI ONLINE DI KOTA MEDAN - Ummu Hajar; Rika Natasya; Ramadhani, Yanti (Zhata Institut, 2024)
Recently, cases of illegal investment or fraud have increased in Indonesia. Illegal investment incidents occur frequently and harm people. It is called illegal because it carries out activities without permission from the relevant institutions. Illegal investment must be stopped because it can cause great losses to society.The research method used in this journal research is a qualitative method with data collection tools with literature studies both offline and online. Investment is regulated in Law Number 25 of 2007 concerning investment. Compensation is a legal way to protect parties who suffer losses.The Indonesian government has ordered the . Financial Services Authority (OJK) to monitor all parties engaged in investment to prevent cases of illegal investment fraud.